Women's experiences of positive postnatal partner support. (15th March 2019) - Kirova, Krasimira; Snell, Tristan
ABSTRACT: Objective : To explore women's experiences of support from their partners in the first year and a half post-baby and identify the particular attitudes and behaviours they considered helpful. Background : Becoming a mother brings major life changes that impact on maternal mental health. Partner support can have a protective effect during this transition period, although there is currently a gap in the research regarding specific examples of partner support that women find helpful. Methods : Six mothers who self-identified as receiving positive partner support took part in semi-structured interviews. Data were analysed using Interpretative Phenomenological Analysis. Results : Three superordinate themes emerged: role navigation, emotional support and teamwork. Role navigation included an attitude of respect and appreciation of the mother role, as well as a shift in the father's priorities to include the whole family. Specific behaviours such as communicating with the mother in an empathic way, offering praise and demonstrating reliability and a willingness to help were seen as emotionally supportive. Teamwork included notions of fairness and equality. Conclusion : The present study extends upon previous research by providing clear examples of what women consider helpful from their partners, including an attitude of respect, placing family first, contributing fairly to household responsibilities, flexibility during the changing stages of child development, and facilitating personal time for mothers. These findings may assist to support new parents through the often difficult transition to parenthood.